HUBUNGAN PERCAYA DIRI SISWA DAN PERHATIAN ORANG TUA DENGAN HASIL BELAJAR MATEMATIKA - Rahma Annida Hidayati; Sumargiyani Sumargiyani (Universitas Muhammadiyah Semarang, 2018)
This research is based on the low self-confidence of students and attention from parents that was lacked at SMP Negeri 1 Kasihan, Bantul Regency. The aims is to find out that there is a positive and significant relationship between the students self-confidence and the attention of the parents with the mathematics learning outcomes of the 8 th grade student of SMP Negeri 1 Kasihan, Bantul Regency in the academic year of 2017/2018. The research population students of class VIII was 164 students. Class VIII D was obtained as a sample class with random sampling technique for the class. Techniques of collecting data used method of questionnaire to obtain data of mathematics result. Theinstrument test includes of validity test, power different test, and reliability test.Analysis prerequisite test incudes of normality test, linearity test, andindependence test. Data analysis using the product moment analysis andmultiple linear regression analysis. The result showed that there was a positive and significant relationship between student confidence and parents attention with the result of mathematics subject of the 8th grade student of SMP Negeri 1 Kasihan, Bantul Regency in the academic year of 2017/2018. It shown by F count > F 0,316 table= 4,222 > 3,32, R = 0,469 and R + 0,039, SR 2 = 0,220 with = 58,045 + = 93,596 % and SR = 6,404 %,SE = 20,559 % and SE = 1,407 %. Keywords: Self-Confidence, Attention of Parents, Mathematics LearningOutcomes